Preparation method and system for 3D printing in-situ cluster reinforced aluminum alloy
By using ball mill mixed powder and nitrogen-protected melt molding in the 3D printing 7075 aluminum alloy process, combined with heat treatment to generate clusters, the problems of thermal cracks and high costs are solved, significantly improving mechanical properties and reducing energy consumption.
Patent Information
- Application Number
- CN202510029163.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
AI Technical Summary
The existing 3D printed 7075 aluminum alloy process has thermal crack problems, affecting mechanical properties, and has high argon protection cost, traditional T6 heat treatment energy consumption, and its mechanical properties are not as good as traditional methods.
Micron-scale 7075 aluminum alloy powder, micron-scale zinc alloy powder, micron-scale aluminum scandium alloy powder and sub-micron zirconium hydride powder were used for ball milling and mixing, melt-forming was carried out under nitrogen protection by 3D printing, and (Zn, Sc, Zr) clusters were generated by heat treatment to improve mechanical properties.
It has achieved no cracks inside the aluminum alloy, the tensile strength reaches 530-545MPa, and the elongation after break is ≥7%, while reducing printing costs and heat treatment energy consumption.
Smart Images

Figure CN119824263A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal additive manufacturing, and in particular relates to a preparation method and system for 3D printing in-situ cluster-reinforced aluminum alloy. Background Art
[0002] 3D printing is a special laser forming technology and one of the most advanced precision forming technologies currently in development. It has broad application prospects in aerospace, automotive, machinery manufacturing, and even biomedicine. Compared with traditional forming technology, 3D printing technology improves material utilization and saves raw material input costs. In particular, laser powder bed fusion (L-PBF) technology can print and process complex parts through digital models, shortening R&D time and improving production efficiency.
[0003] Aluminum alloy is based on aluminum metal, and can add a certain amount of other alloying elements to make it have the advantages of low density, high strength, good electrical conductivity and thermal conductivity, etc. It is widely used in the fields of shipbuilding, chemical industry, aerospace, etc. 7xxx aluminum alloy is a kind of aluminum alloy, which is a super-hard aluminum alloy, especially 7075 aluminum alloy, which is widely used in aerospace, mechanical equipment and other fields because of its good mechanical properties and processing properties. However, compared with other materials successfully used in LPBF, 7 series aluminum alloy has higher thermal conductivity and higher reflectivity to laser, and has the characteristics of high alloying degree and wide crystallization range, which makes 7075 aluminum alloy prepared by 3D printing have thermal cracks, which seriously affects the mechanical properties of 7075 aluminum alloy and limits the application of 7075 aluminum alloy.
[0004] At present, there are some technologies that can realize 3D printing of 7075 aluminum alloy, such as:
[0005] A 3D printed 7xxx aluminum alloy and a preparation method thereof (publication number CN108330344B) in which the 7xxx aluminum alloy includes Si, Fe, Cu, Mn, Mg, Cr, Zn, Ti, Zr, and Sc, wherein, by mass percentage, the Si content is 0.1-6.0%, the Fe content is 0-6.0%, the Cu content is 1.2-6.0%, the Mn content is 0.1-6.3%, the Mg content is 2.1-6.9%, the Cr content is 0.18-0.68%, the Zn content is 5.1-10.1%, the Ti content is 0-6.2%, the Zr content is 0-6.0%, the Sc content is 0-1%, and the remainder is Al. The surface of the aluminum alloy workpiece after 3D printing of the invention is smooth and crack-free.
[0006] A composite powder capable of realizing crack-free SLM forming of 7075 aluminum alloy and its preparation method and application (CN110508805A) discloses a composite powder capable of realizing crack-free SLM forming of 7075 aluminum alloy and its preparation method and application. The method comprises: mixing nano-ceramic particles, submicron hydride particles,
[0007] 7075 aluminum alloy powder and ball milling medium are added to a vacuum ball milling tank, and ball milled in an inert gas to obtain a composite powder that can achieve crack-free SLM forming of 7075 aluminum alloy. The preparation method of the present invention is simple and efficient, with low cost, and the obtained dual-phase particle-modified 7075 aluminum alloy composite powder has low oxygen content, and the matrix powder maintains good sphericity and good fluidity. While achieving crack-free SLM forming, it also well meets the requirements of 3D printing for powder performance. Among them, submicron hydride particles generate nucleating agents through in-situ reactions during the melting process to promote heterogeneous nucleation of the melt and refine the grains; nano-ceramic particles as nucleating agents can also promote heterogeneous nucleation of the melt, and the nano-ceramic particles also play the role of reinforcing phase.
[0008] A high-strength 7-series aluminum-based composite material for 3D printing and its preparation method (CN111842890R) The invention discloses a high-strength 7-series aluminum-based composite material for 3D printing and its preparation method, wherein: a method for preparing a high-strength 7-series aluminum-based composite powder for powder bed 3D printing, wherein: the 7-series aluminum-based composite powder includes 7-series aluminum alloy powder, copper-based shape memory alloy powder, and oxidized bait powder; the 7-series aluminum alloy powder, the copper-based shape memory alloy powder, and the oxidized bait powder are loaded into a powder mixing device and mixed evenly, and the 7-series aluminum-based composite powder is obtained by sieving after drying, and the powder can be used for powder bed laser 3D printing; by mass fraction, the oxidized bait powder is 0.1-1%, the copper-based shape memory alloy powder is 0.1-3%, and the remainder is the 7-series aluminum alloy powder. The invention eliminates cracks in the 7-series aluminum alloy prepared by the SLM method and improves its mechanical properties by adding copper-based shape memory alloy and oxidized bait.
[0009] At present, these preparation methods all use argon protection to complete the process window and prepare, and the heat treatment uses the traditional T6 process, but the mechanical properties are still somewhat different from those of the 7075 aluminum alloy prepared by the traditional method. Therefore, it is necessary to develop a method for 3D printing 7075 aluminum alloy and its supporting heat treatment process to improve the mechanical properties and expand the application of 7 series aluminum alloy in the field of LPBF printing.
[0010] Through the above analysis, the problems and defects of the prior art are as follows:
[0011] At present, these processes all use argon as the protective gas during the printing process. Because the preparation and use costs of argon are high, and as the printing size increases, the gas consumption will also increase, thus indirectly increasing the printing cost. The traditional T6 heat treatment has a long heating time and high energy consumption, which makes the post-processing of parts complicated and costly, and the mechanical properties are still somewhat different from those of the 7075 aluminum alloy prepared by traditional methods. Summary of the invention
[0012] In view of the problems existing in the prior art, the present invention provides a preparation method of 3D printed in-situ cluster reinforced aluminum alloy.
[0013] The present invention is achieved in this way: a preparation method of 3D printed in-situ cluster reinforced aluminum alloy comprises:
[0014] Step 1, ball-milling and mixing micron-sized 7075 aluminum alloy powder, micron-sized zinc alloy powder, micron-sized aluminum-scandium alloy powder and submicron zirconium hydride powder, and then drying to obtain an aluminum-based composite powder;
[0015] Step 2, adjusting 3D printing parameters, making according to the 3D model data of the part in a printing device with nitrogen gas, and obtaining a printed product after melting the powder;
[0016] Step 3: subject the printed product to a heat treatment process to obtain the final 3D printed aluminum-based alloy.
[0017] Further, the content of the micron-sized zinc alloy powder is 7.5-8.5%, the content of the micron-sized aluminum-scandium alloy powder is 38-42%, the content of the submicron-sized zirconium hydride powder is 0.6-0.8%, and the balance is micron-sized 7075 aluminum alloy powder;
[0018] The aluminum-based composite powder is ball-milled in a vacuum using an intermittent low-energy ball-milling process. ZrO2 ceramic balls are used as the ball-milling medium, with a ball-to-material mass ratio of 1:1. The ball-to-material is composed of two types of ceramic balls with diameters of 6 mm and 3 mm, with a mass ratio of 1:2. Each ball-milling takes 4-5 hours, followed by air cooling for 0.4-0.6 hours, alternating with a ball speed of 70-80 r / min, and a total of 16-20 hours of powder mixing.
[0019] Furthermore, the mixed aluminum-based composite powder is dried in a vacuum tube environment for 4-6 hours at a drying temperature of 80-100°C.
[0020] Further, the laser spot is 90-110um, the laser power is 150-170W, the scanning rate is 250-350mm / s, the printing layer thickness is 25-35um, the scanning spacing is 70-90um, the printing strategy is checkerboard or stripe, the preheating is 180-220℃, and the oxygen content is less than 100ppm;
[0021] Solution treatment is carried out at 325-375℃ under vacuum for 2-3 hours, followed by water quenching, with a transfer time of 8-10s, and finally left standing indoors for 11-13 days at a room temperature between 15-35℃.
[0022] Furthermore, the powder raw material includes the following chemical elements: Zn: 99-98%, X: 1-2%; the X element includes: Al, Mn, Cu, Mg, Ag, In; the particle size of the micron-grade zinc alloy powder is 15-53um, and it is spherical;
[0023] The powder raw material includes the following chemical elements: Al: 98.2-97.8%, Sc: 1.8-2.2%; the particle size of the micron-grade aluminum-scandium alloy powder is 15-53um and spherical;
[0024] The powder raw material includes the following chemical elements: Zn: 5.1-6.1%, Mg: 2.1-3%, Cu: 1.2-2%, Cr: 0.18-0.28%, Si: ≤0.35%, Fe: ≤0.35%, Ti: ≤0.4%, and the rest is aluminum; the particle size of the micron-grade aluminum alloy powder is 15-53um and spherical;
[0025] The particle size of the submicron zirconium hydride powder is 500 nm.
[0026] Furthermore, there are no cracks inside the aluminum alloy, the tensile strength can reach 530-545Mpa, and the elongation after fracture is above 7±1.2%.
[0027] The present invention also provides a preparation system for 3D printing in-situ cluster-reinforced aluminum alloy, the system comprising:
[0028] Powder mixing and ball milling module: used to mix micron-grade 7075 aluminum alloy powder, micron-grade zinc alloy powder, micron-grade aluminum-scandium alloy powder and submicron-grade zirconium hydride powder according to a set ratio, and ball mill them through an intermittent low-energy ball milling process. The ball milling medium uses ZrO2 ceramic balls, and the ball-to-material mass ratio is 1:1;
[0029] Powder drying module: used to dry the mixed aluminum-based composite powder in a vacuum tube environment, with a drying time of 4-6 hours and a drying temperature of 80-100°C;
[0030] 3D printing module: equipped with a dual-channel laser selective melting device, capable of high-precision printing with a printing layer thickness of 25-35μm, a scanning pitch of 70-90μm, and a laser power of 150-170W, supporting checkerboard or stripe printing strategies, and equipped with a printing chamber with nitrogen gas to control the oxygen content below 100ppm;
[0031] Heat treatment module: used to perform solution treatment at 325-375℃ for 2-3 hours on 3D printed products, and optimize heat treatment through a process of water quenching, transfer and room temperature standing for 11-13 days.
[0032] Further, the powder mixing and ball milling module comprises:
[0033] Automatic batching device: used to accurately control the proportion of micron-grade zinc alloy powder, micron-grade aluminum-scandium alloy powder and submicron-grade zirconium hydride powder. The content of zinc alloy powder is 7.5-8.5%, the content of aluminum-scandium alloy powder is 38-42%, the content of zirconium hydride powder is 0.6-0.8%, and the balance is 7075 aluminum alloy powder;
[0034] Ball mill control device: capable of adjusting the ball mill speed (70-80r / min), time (16-20 hours), air cooling interval (0.4-0.6 hours) and ceramic ball diameter ratio (the mass ratio of 6mm and 3mm is 1:2) according to the preset program;
[0035] Vacuum sealing system: ensures a sealed environment during powder mixing to avoid oxidation and contamination.
[0036] Furthermore, the 3D printing module includes:
[0037] Laser control system: used to adjust the laser spot size to 90-110μm and the laser scanning rate to 250-350mm / s;
[0038] Print bed: Use a heated print bed with a temperature range of 180-220°C to improve the adhesion of the printed layer;
[0039] Gas control system: can introduce high-purity nitrogen into the printing chamber to control the oxygen content in the chamber to be less than 100ppm;
[0040] Positioning and strategy control module: supports automatic generation of printing paths, and selects checkerboard or strip printing strategies according to different models to achieve multi-directional distribution optimization of reinforced fibers.
[0041] Further, the heat treatment module comprises:
[0042] Solution treatment unit: used for solution treatment of printed products at 325-375℃, with a treatment time of 2-3 hours;
[0043] Rapid quenching unit: used for rapid quenching in water, with a transfer time of less than 10 seconds;
[0044] Room temperature static unit: static for 11-13 days at room temperature of 15-35℃ for natural aging and microstructure optimization;
[0045] Microscopic inspection module: integrated scanning electron microscope (SEM) and X-ray diffractometer (XRD) to detect whether there are cracks inside the aluminum alloy and verify the tensile strength (530-545MPa) and elongation after fracture (≥7%).
[0046] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:
[0047] First, the technical solution adopted by the present invention is: a preparation method of 3D printed in-situ cluster-reinforced aluminum alloy, wherein the in-situ cluster reinforcement requires a mixture of micron-grade 7075 aluminum alloy powder, micron-grade zinc alloy powder, micron-grade aluminum-scandium alloy powder and submicron zirconium hydride powder, which is ball-milled by an intermittent low-energy ball milling process under vacuum to obtain a uniformly distributed powder; Al3 (Sc, Zr) heterogeneous nucleation is generated in situ in a low-oxygen environment by powder bed fusion 3D printing technology to eliminate thermal cracks of 7 series aluminum alloys and improve forming quality; (Zn, Sc, Zr) clusters and common clusters are generated at grain boundaries by a heat treatment process to further improve their mechanical properties.
[0048] 1. The present invention provides a method for preparing 3D printed in-situ cluster-reinforced aluminum alloys. The mixed powder process avoids the complex process of melting multiple elements together. The nitrogen printing avoids the high cost caused by the increased argon consumption when printing large parts. The energy consumption time of heat treatment is shortened to reduce the energy consumption caused by heat treatment. The present invention can obtain high-strength and high-toughness 7-series aluminum alloy 3D printed products in large quantities at low cost, thereby promoting a wider application of the products.
[0049] 2. Zn, Zr and Sc are added to the powder raw materials used in the present invention, and through the processing principle of rapid melting and solidification of 3D printing, a fine Al3 (Sc, Zr) heterogeneous nucleus can be formed at the boundary of the aluminum alloy molten pool, reducing thermal stress, eliminating thermal cracks of 7075 aluminum alloy during processing, and improving the forming quality. After solution treatment at a suitable temperature, internal stress can be eliminated. On the one hand, a solid solution can be formed, and on the other hand, heterogeneous nucleation will not grow due to excessive temperature and reduce fine grain strengthening. Then natural aging is carried out to increase the hardness in a short time. The main source of hardening of the Al-Zn-Mg-Cu-Sc-Zr alloy in the present invention is the formation of grain boundary precipitates, which are strongly affected by in-situ cluster nucleation. (Zn, Sc, Zr) clusters and common clusters are formed during the natural aging process. As the number of clusters formed during the natural aging process increases, the precipitates are refined during the aging process, which helps to increase the hardness. After heat treatment, the overall strength and toughness of 3D printed 7075 aluminum alloy are improved, providing new ideas for the development of 3D printed 7 series.
[0050] Second, as auxiliary evidence of the inventiveness of the claims of the present invention, it is also reflected in the following important aspects:
[0051] (1) The expected benefits and commercial value of the technical solution of the present invention after transformation are:
[0052] The technical solution of the present invention can reduce the use and consumption of argon gas by using nitrogen as the protective gas, while ensuring that the 7075 powder meets certain mechanical properties through 3D printing technology. It can also reduce environmental pollution and printing costs. Through the natural aging heat treatment method, the heat treatment time, process and energy consumption are reduced. The technical solution of the present invention has a lower printing cost than other similar solutions and has certain commercial value.
[0053] (2) The technical solution of the present invention fills the technical gap in the industry at home and abroad:
[0054] The technical solution of the present invention is formed by laser powder bed melting technology under nitrogen protection, and maintains relatively excellent mechanical properties while simplifying the heat treatment process. At present, it fills the gap in the low-cost preparation of 7 series aluminum alloys at home and abroad through in-situ cluster strengthening under laser powder bed melting technology.
[0055] (3) Whether the technical solution of the present invention solves the technical problems that people have been eager to solve but have not been able to solve successfully:
[0056] Because 7 series aluminum alloys are difficult to form through laser powder bed fusion technology, have poor mechanical properties, and high printing costs. The technical solution of the present invention reduces printing costs while obtaining excellent mechanical properties, providing a new idea for the development of 3D printing 7 series aluminum alloys.
[0057] The technical solution of the present invention overcomes the technical prejudice of high cost of argon printing and low mechanical properties of traditional heat treatment technology solutions. Starting from the forming characteristics of laser powder bed melting technology, an in-situ cluster strengthening method is proposed, and a low-cost preparation technology solution with excellent mechanical properties is invented.
[0058] Third, the present invention solves the performance bottleneck problem of traditional aluminum alloy materials in the 3D printing process caused by uneven microstructure, excessive residual stress and insufficient toughness by accurately optimizing the preparation parameters of 3D printing in-situ cluster-reinforced aluminum alloy. The specific parameter optimization includes:
[0059] 1) Powder preparation and mixing parameters:
[0060] -The content of micron-grade zinc alloy powder is controlled at 7.5-8.5%, aluminum-scandium alloy powder is 38-42%, submicron zirconium hydride powder is 0.6-0.8%, and the balance is 7075 aluminum alloy powder.
[0061] - The ball mill uses ZrO2 ceramic balls, the ball-to-material mass ratio is 1:1, the mass ratio of 6mm and 3mm balls is 1:2, and the ball mill speed is 70-80r / min. The intermittent ball milling process (ball milling for 4-5 hours, air cooling for 0.4-0.6 hours) is used to achieve uniform powder mixing, and the total powder mixing time is 16-20 hours.
[0062] - The powder is dried in a vacuum environment for 4-6 hours at a temperature of 80-100°C to ensure that the powder is pure and has no moisture absorption problem.
[0063] 2) 3D printing process parameters:
[0064] - Laser spot diameter 90-110μm, power 150-170W, scanning rate 250-350mm / s, printing layer thickness 25-35μm, scanning spacing 70-90μm.
[0065] - The printing strategy uses a checkerboard or strip pattern, and the substrate preheat temperature is set at 180-220°C to ensure that residual stress is minimized during the printing process and the oxygen content is less than 100ppm.
[0066] 3) Heat treatment process parameters:
[0067] -Solution treatment temperature is controlled at 325-375℃, treatment time is 2-3 hours, followed by water quenching, transfer time is controlled within 8-10 seconds;
[0068] -Finally, let it stand at room temperature (15-35°C) for 11-13 days to complete the stabilization of the material structure.
[0069] Technical issues solved:
[0070] 1) Powder mixing uniformity and microstructure control:
[0071] Traditional aluminum alloy powders are prone to grain coarsening and performance degradation in 3D printing due to uneven component distribution. The present invention significantly improves the uniformity of aluminum-based composite powders by optimizing ball milling processes (such as ceramic ball ratio, intermittent process, vacuum drying) and component design, ensuring uniform distribution of alloy elements during printing and forming a refined grain structure.
[0072] 2) Residual stress and defects during printing:
[0073] By adjusting the laser spot, power, scanning strategy and preheating temperature, the present invention effectively reduces the residual stress during the printing process and avoids the generation of internal cracks. At the same time, nitrogen protection and low oxygen content control improve the density of aluminum-based alloys and significantly reduce the generation of pores and inclusions.
[0074] 3) Performance optimization and strengthening mechanism:
[0075] Submicron-grade zirconium hydride powder and micron-grade aluminum-scandium alloy powder are used to form in-situ clusters during the printing process, achieving multiple strengthening mechanisms of grain refinement, cluster strengthening and precipitation strengthening. Heat treatment optimization makes the precipitation phase inside the material evenly distributed, further improving the strength and toughness.
[0076] Significant technological advances achieved:
[0077] 1) Mechanical properties are significantly improved:
[0078] Through the above optimization, the 3D printed aluminum-based alloy prepared by the present invention has excellent mechanical properties, with a tensile strength of 530-545MPa and a stable elongation after fracture of more than 7±1.2%. Compared with traditional aluminum alloys, the strength and ductility are greatly improved, and it is suitable for engineering applications with high strength and high toughness requirements.
[0079] 2) Uniform organization and crack-free structure:
[0080] The optimized preparation method ensures that there are no defects such as cracks, pores and inclusions inside the aluminum alloy, the microstructure is uniform, and the grains are fine, providing a guarantee for high-reliability structural parts.
[0081] 3) Broad industrial application prospects:
[0082] The reinforced aluminum alloy prepared by the present invention combined with the 3D printing process can be widely used in the fields of aerospace, automobile manufacturing and high-performance mechanical parts manufacturing, providing efficient, economical and high-performance solutions and promoting the development of advanced manufacturing technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0083] Figure 1 It is a flow chart of the preparation method of 3D printing in-situ cluster reinforced aluminum alloy provided by an embodiment of the present invention.
[0084] Figure 2 It is a schematic diagram of the process flow of a method for preparing a 3D printed in-situ cluster-reinforced aluminum alloy provided by an embodiment of the present invention;
[0085] Figure 3 This is a microscopic morphology of the mixed powder after ball milling and drying provided by an embodiment of the present invention;
[0086] Figure 4 is a metallographic structure diagram after 3D printing provided by an embodiment of the present invention;
[0087] Figure 5 is a SEM image after printing provided by an embodiment of the present invention;
[0088] Figure 6 is a SEM image after heat treatment provided by an embodiment of the present invention;
[0089] Figure 7 It is a stress-strain curve provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0090] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0091] like Figure 1 As shown, a method for preparing a 3D printed in-situ cluster-reinforced aluminum alloy provided by an embodiment of the present invention comprises the following steps:
[0092] S101, ball-milling and mixing micron-sized 7075 aluminum alloy powder, micron-sized zinc alloy powder, micron-sized aluminum-scandium alloy powder and submicron-sized zirconium hydride powder, and drying to obtain an aluminum-based composite powder;
[0093] S102, adjusting 3D printing parameters, and manufacturing according to the three-dimensional model data of the part in a printing device into which nitrogen is introduced, to obtain a printed product after melting the powder;
[0094] S103, subjecting the printed product to a heat treatment process to obtain a final 3D printed aluminum-based alloy.
[0095] The method of the present invention firstly ball-mills micron-sized 7075 aluminum alloy powder, micron-sized zinc alloy powder, micron-sized aluminum-scandium alloy powder and submicron-sized zirconium hydride powder to ensure that each component is evenly distributed in the aluminum-based composite powder. During the ball milling process, high-speed mechanical impact and friction are used to homogenize the powder particles within the nanoscale range, and the trace hydrogen decomposed by zirconium hydride can promote the formation and distribution of clusters in the subsequent printing process. The mixed powder is dried to ensure that it meets the requirements of the 3D printing process and avoids printing quality problems caused by moisture absorption of the powder.
[0096] The prepared aluminum-based composite powder is input into a 3D printing device protected by nitrogen, and the selective laser melting (SLM) technology or electron beam melting (EBM) technology is used to print and shape the part layer by layer according to the 3D model data of the part. During the printing process, the high-energy beam (laser or electron beam) melts the powder locally and solidifies it quickly to form a dense microstructure. Due to the decomposition behavior of zirconium hydride during the printing process, nanoscale Zr group clusters are formed in the microstructure, which effectively improves the strength and hardness of the aluminum-based alloy. In addition, the nitrogen protective atmosphere avoids oxidation reactions at high temperatures, ensuring the purity and performance of the printed product.
[0097] After printing, the product is heat treated to further optimize its microstructure. Heat treatment promotes the uniform distribution of alloy elements through heating and heat preservation, and strengthens the nucleation behavior of Zr clusters. During the heat treatment, the Sc element precipitated in the aluminum-scandium alloy further promotes the formation of fine grains and improves the fine grain strengthening effect of the material. This stage significantly improves the mechanical properties of the aluminum-based alloy, including its strength, ductility and heat resistance.
[0098] The final 3D printed aluminum-based alloy has the comprehensive performance advantages of fine grain strengthening, solid solution strengthening and cluster strengthening. The synergistic effect of nano-scale Zr clusters and Sc elements effectively improves the grain refinement of the material and enhances the mechanical properties of the alloy; at the same time, the uniform distribution of micron-scale zinc and aluminum-scandium alloys provides a good solid solution strengthening effect. Combined with the high-degree-of-freedom molding process of 3D printing, the prepared aluminum-based alloy has a wide range of application value in aerospace, automotive industry and other fields.
[0099] The micron-grade zinc alloy powder provided in the embodiment of the present invention has a content of 7.5-8.5%, the micron-grade aluminum-scandium alloy powder has a content of 38-42%, the submicron-grade zirconium hydride powder has a content of 0.6-0.8%, and the balance is micron-grade 7075 aluminum alloy powder;
[0100] The aluminum-based composite powder is ball-milled in a vacuum using an intermittent low-energy ball-milling process. ZrO2 ceramic balls are used as the ball-milling medium, with a ball-to-material mass ratio of 1:1. The ball-to-material is composed of two types of ceramic balls with diameters of 6 mm and 3 mm, with a mass ratio of 1:2. Each ball-milling takes 4-5 hours, followed by air cooling for 0.4-0.6 hours, alternating with a ball speed of 70-80 r / min, and a total of 16-20 hours of powder mixing.
[0101] The mixed aluminum-based composite powder provided in the embodiment of the present invention is dried in a vacuum tube environment for 4-6 hours at a drying temperature of 80-100°C.
[0102] The laser spot provided by the embodiment of the present invention is 90-110um, the laser power is 150-170W, the scanning rate is 250-350mm / s, the printing layer thickness is 25-35um, the scanning spacing is 70-90um, the printing strategy is checkerboard or stripe, the preheating is 180-220°C, and the oxygen content is less than 100ppm;
[0103] Solution treatment is carried out at 325-375℃ under vacuum for 2-3 hours, followed by water quenching, with a transfer time of 8-10s, and finally left standing indoors for 11-13 days at a room temperature between 15-35℃.
[0104] The powder raw material provided in the embodiment of the present invention includes the following chemical elements: Zn: 99-98%, X: 1-2%; the X element includes: Al, Mn, Cu, Mg, Ag, In; the particle size of the micron-grade zinc alloy powder is 15-53um, and it is spherical;
[0105] The powder raw material includes the following chemical elements: Al: 98.2-97.8%, Sc: 1.8-2.2%; the particle size of the micron-grade aluminum-scandium alloy powder is 15-53um and spherical;
[0106] The powder raw material includes the following chemical elements: Zn: 5.1-6.1%, Mg: 2.1-3%, Cu: 1.2-2%, Cr: 0.18-0.28%, Si: ≤0.35%, Fe: ≤0.35%, Ti: ≤0.4%, and the rest is aluminum; the particle size of the micron-grade aluminum alloy powder is 15-53um and spherical;
[0107] The particle size of the submicron zirconium hydride powder is 500 nm.
[0108] The aluminum alloy provided by the embodiment of the present invention has no cracks inside, has a tensile strength of 530-545 MPa, and has an elongation after fracture of more than 7±1.2%.
[0109] like Figure 2 As shown, the preparation method of the 3D printed in-situ cluster reinforced aluminum alloy of the present invention includes three main process stages: mixed powder preparation, 3D printing molding, and heat treatment. First, micron-grade aluminum-based powder and submicron zirconium hydride powder are mixed by ball milling to obtain a uniform composite powder. Subsequently, the laser selective melting technology is used to print and mold layer by layer under nitrogen protection, and finally the printed part is subjected to a heat treatment process to optimize its organizational properties. The entire process design is highly integrated and suitable for the precision manufacturing of complex parts.
[0110] Embodiment 1:
[0111] The first step is to prepare powder materials. In terms of mass percentage, the content of micron-grade zinc alloy powder is 7.9%, the content of micron-grade aluminum-scandium alloy powder is 40%, the content of submicron zirconium hydride powder is 0.74%, and the balance is micron-grade 7075 aluminum alloy powder.
[0112] In the second step, the aluminum-based composite powder is ball-milled in a vacuum using an intermittent low-energy ball-milling process. ZrO2 ceramic balls are used as the ball-milling medium, and the ball-to-material mass ratio is 1:1. The ball-to-material is composed of two types of ceramic balls with diameters of 6 mm and 3 mm, and the mass ratio is 1:2. Each ball-milling is performed for 4 hours, followed by air cooling for 0.5 hours, alternating with a ball speed of 80 r / min, and the powder is mixed for a total of 16 hours.
[0113] The third step is to dry the ball-milled powder. The mixed aluminum-based composite powder is dried in a vacuum tube environment for 5 hours at a drying temperature of 90°C.
[0114] The fourth step is to set the printing parameters: laser spot size 100um, laser power 160W, scanning rate 300mm / s, printing layer thickness 30um, scanning spacing 80um, printing strategy as checkerboard, preheating 200℃, and oxygen content less than 100ppm.
[0115] The fifth step is to carry out heat treatment process, carry out solution treatment at 350℃ under vacuum for 2 hours, then water quench, transfer time is within 8s, and finally stand indoors for 12 days, with the indoor temperature between 15-35℃.
[0116] Embodiment 2:
[0117] The difference from Example 1 is that, in this embodiment, the powder material is configured, and by mass percentage, the content of micron-grade zinc alloy powder is 8.2%, the content of micron-grade aluminum-scandium alloy powder is 41%, the content of submicron zirconium hydride powder is 0.72%, and the balance is micron-grade 7075 aluminum alloy powder.
[0118] Embodiment 3:
[0119] The difference from Example 1 is that in this embodiment, the ball milling is performed for 5 hours each time and air cooling is performed for 0.5 hours, alternately, the grinding ball speed is 80r / min, and the powder is mixed for a total of 20 hours. The powder does not deform and maintains a good sphericity.
[0120] Embodiment 4:
[0121] The difference from Example 1 is that in this embodiment, the printing parameters are set as follows: laser spot 80um, laser power 170W, scanning rate 250mm / s, printing layer thickness 30um, scanning spacing 80um, printing strategy is checkerboard, preheating 180°C, and oxygen content less than 100ppm.
[0122] Embodiment 5:
[0123] The difference from Example 1 is that in this embodiment, a heat treatment process is carried out, solution treatment is performed at 360°C for 2 hours under vacuum, followed by water quenching, the transfer time is within 10 seconds, and finally the mixture is left standing indoors for 12 days at an indoor temperature between 15-35°C.
[0124] like Figure 3As shown in the figure, the mixed powder after ball milling and drying has uniform particle size distribution and surface characteristics. The microscopic morphology shows that the powders of each component are fully mixed, with micron-sized 7075 aluminum alloy powder as the matrix, and micron-sized aluminum-scandium alloy powder, zinc alloy powder and submicron zirconium hydride powder uniformly distributed in the mixed system. This uniformity lays the foundation for uniform melting and subsequent grain refinement during the printing process.
[0125] like Figure 4 As shown in the figure, the metallographic structure diagram after 3D printing shows that there are no cracks inside the material. The fine grain structure formed by rapid melting and cooling during the printing process, as well as the fine crystal precipitation of scandium and zirconium elements, inhibit the generation of cracks. The organizational characteristics of the printed parts verify the effectiveness of the process parameters on material forming.
[0126] like Figure 5 As shown in the figure, the SEM image after printing shows the microstructure characteristics of the material. During the printing process, due to the precipitation of Sc and Zr elements, a fine grain area is formed at the edge of the molten pool, which effectively inhibits the occurrence of cracks. The scanning results show that the microstructure has a typical bimodal structure, which provides a good initial organizational foundation for subsequent heat treatment.
[0127] like Figure 6 As shown in the figure, the SEM image after heat treatment reveals that the material structure is significantly optimized after solid solution and aging treatment. Clusters are precipitated at the grain boundaries to strengthen the interface bonding strength between crystals. Heat treatment improves the strength and toughness of the material, providing key support for the final material performance improvement.
[0128] like Figure 7 As shown in the figure, the stress-strain curve verifies the mechanical properties of the material prepared by the process. After heat treatment, the printed part shows significant strength and ductility, and has excellent tensile properties and plastic deformation ability. The high tensile strength and yield strength shown in the curve indicate that the preparation process of the present invention can significantly improve the comprehensive performance of 7075 aluminum alloy materials and meet the needs of the aerospace and automotive industries for high-performance materials.
[0129] The system first completes the precise proportioning and uniform mixing of powders through the powder mixing and ball milling module. The automatic batching device accurately controls the contents of 7075 aluminum alloy powder, zinc alloy powder, aluminum scandium alloy powder and zirconium hydride powder, which are the remainder, 7.5-8.5%, 38-42% and 0.6-0.8% respectively. The ball milling control device adjusts the ball milling speed (70-80r / min), ball milling time (16-20 hours) and air cooling interval (0.4-0.6 hours) according to the preset program. By using ZrO2 ceramic balls (6mm and 3mm diameter mass ratio of 1:2) as ball milling media, uniform distribution of powder and pre-forming of nanoclusters are achieved in a vacuum sealed system while avoiding oxidation and contamination. Subsequently, the mixed powder is dried at 80-100°C in a vacuum tube environment for 4-6 hours to ensure its purity and adaptability to subsequent printing processes.
[0130] The mixed aluminum-based composite powder is used to complete the high-precision printing of parts through the 3D printing module. The printing equipment adopts laser selective melting (SLM) technology. The laser control system sets the laser spot size to 90-110μm, the laser power to 150-170W, the scanning rate to 250-350mm / s, the printing layer thickness to 25-35μm, and the scanning spacing to 70-90μm. High-purity nitrogen is introduced into the printing equipment, and the gas control system ensures that the oxygen content is less than 100ppm to reduce the degradation of material properties caused by oxidation. In order to further reduce the residual stress of the printing layer, the heated printing equipment maintains the substrate temperature at 180-220℃. The printing strategy supports checkerboard and strip modes. The positioning and strategy control module optimizes the printing path to achieve multi-directional distribution of reinforcing fibers and improve the anisotropic mechanical properties of the printed parts.
[0131] The printed product is optimized for microstructure through a heat treatment module. First, a solution treatment at 325-375°C is carried out in a solution treatment unit for 2-3 hours to promote the dissolution and uniform distribution of the strengthening phase. Subsequently, the printed part is quickly quenched in water through a rapid quenching unit, with a transfer time of less than 10 seconds to maintain the uniformity and strength of the alloy structure. Finally, it is left to stand at room temperature (15-35°C) for 11-13 days to complete the natural aging process, further stabilize the microstructure, and improve the comprehensive performance of the material. Through heat treatment optimization, the in-situ clusters and fine-grained structures inside the material significantly improve the mechanical properties.
[0132] After the heat treatment is completed, the product is subjected to quality verification and performance evaluation through the microscopic inspection module. A scanning electron microscope (SEM) and a metallographic microscope (OM) are used to detect whether there are defects such as cracks and pores inside to ensure the density and uniformity of the material. Subsequently, the tensile strength (530-545MPa) and elongation after fracture (≥7%) of the product are verified by a mechanical testing machine to ensure that the material meets the application requirements of high strength and high toughness. The entire system provides a reliable solution for the industrial production of high-performance 3D printed in-situ cluster-reinforced aluminum alloys by optimizing the entire process from powder preparation to performance testing.
[0133] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a 3D printed in-situ cluster-reinforced aluminum alloy, characterized in that: The following steps are involved: Step 1, ball-milling and mixing micron-sized 7075 aluminum alloy powder, micron-sized zinc alloy powder, micron-sized aluminum-scandium alloy powder and submicron zirconium hydride powder, and then drying to obtain an aluminum-based composite powder; Step 2, adjusting 3D printing parameters, making according to the 3D model data of the part in a printing device with nitrogen gas, and obtaining a printed product after melting the powder; Step 3: subject the printed product to a heat treatment process to obtain the final 3D printed aluminum-based alloy.
2. The method for preparing 3D printed in-situ cluster-reinforced aluminum alloy according to claim 1, characterized in that: The content of the micron-sized zinc alloy powder is 7.5-8.5%, the content of the micron-sized aluminum-scandium alloy powder is 38-42%, the content of the submicron-sized zirconium hydride powder is 0.6-0.8%, and the balance is micron-sized 7075 aluminum alloy powder; The aluminum-based composite powder is ball-milled in a vacuum using an intermittent low-energy ball-milling process. ZrO2 ceramic balls are used as the ball-milling medium, with a ball-to-material mass ratio of 1:
1. The ball-to-material is composed of two types of ceramic balls with diameters of 6 mm and 3 mm, with a mass ratio of 1:
2. Each ball-milling takes 4-5 hours, followed by air cooling for 0.4-0.6 hours, alternating with a ball speed of 70-80 r / min, and a total of 16-20 hours of powder mixing.
3. The method for preparing 3D printed in-situ cluster-reinforced aluminum alloy according to claim 1, characterized in that: The mixed aluminum-based composite powder is dried in a vacuum tube environment for 4-6 hours at a drying temperature of 80-100°C.
4. The method for preparing 3D printed in-situ cluster reinforced aluminum alloy according to claim 1, characterized in that: Laser spot 90-110um, laser power 150-170W, scanning rate 250-350mm / s, printing layer thickness 25-35um, scanning spacing 70-90um, printing strategy is checkerboard or stripe, preheating 180-220℃, oxygen content less than 100ppm; Solution treatment is carried out at 325-375℃ under vacuum for 2-3 hours, followed by water quenching, with a transfer time of 8-10s, and finally left standing indoors for 11-13 days at a room temperature between 15-35℃.
5. The method for preparing 3D printed in-situ cluster reinforced aluminum alloy as claimed in claim 2, characterized in that: The powder raw material includes the following chemical elements: Zn: 99-98%, X: 1-2%; the X element includes: Al, Mn, Cu, Mg, Ag, In; the particle size of the micron-grade zinc alloy powder is 15-53um, and it is spherical; The powder raw material includes the following chemical elements: Al: 98.2-97.8%, Sc: 1.8-2.2%; the particle size of the micron-grade aluminum-scandium alloy powder is 15-53um and spherical; The powder raw material includes the following chemical elements: Zn: 5.1-6.1%, Mg: 2.1-3%, Cu: 1.2-2%, Cr: 0.18-0.28%, Si: ≤0.35%, Fe: ≤0.35%, Ti: ≤0.4%, and the rest is aluminum; the particle size of the micron-grade aluminum alloy powder is 15-53um and spherical; The particle size of the submicron zirconium hydride powder is 500 nm.
6. The method for preparing 3D printed in-situ cluster reinforced aluminum alloy according to claim 1, characterized in that: There are no cracks inside the aluminum alloy, the tensile strength can reach 530-545Mpa, and the elongation after fracture is above 7±1.2%.
7. A preparation system for 3D printing in-situ cluster-reinforced aluminum alloy, characterized in that: The system includes: Powder mixing and ball milling module: used to mix micron-grade 7075 aluminum alloy powder, micron-grade zinc alloy powder, micron-grade aluminum-scandium alloy powder and submicron-grade zirconium hydride powder according to a set ratio, and ball mill them through an intermittent low-energy ball milling process. The ball milling medium uses ZrO2 ceramic balls, and the ball-to-material mass ratio is 1:1; Powder drying module: used to dry the mixed aluminum-based composite powder in a vacuum tube environment, with a drying time of 4-6 hours and a drying temperature of 80-100°C; 3D printing module: equipped with a dual-channel laser selective melting device, capable of high-precision printing with a printing layer thickness of 25-35μm, a scanning pitch of 70-90μm, and a laser power of 150-170W, supporting checkerboard or stripe printing strategies, and equipped with a printing chamber with nitrogen gas to control the oxygen content below 100ppm; Heat treatment module: used to perform solution treatment of 3D printed products at 325-375℃ for 2-3 hours, and optimize heat treatment through a process of water quenching, transfer and room temperature standing for 11-13 days.
8. The preparation system for 3D printing in-situ cluster-reinforced aluminum alloy according to claim 7, characterized in that: The powder mixing and ball milling module comprises: Automatic batching device: used to accurately control the proportion of micron-grade zinc alloy powder, micron-grade aluminum-scandium alloy powder and submicron-grade zirconium hydride powder. The content of zinc alloy powder is 7.5-8.5%, the content of aluminum-scandium alloy powder is 38-42%, the content of zirconium hydride powder is 0.6-0.8%, and the balance is 7075 aluminum alloy powder; Ball mill control device: capable of adjusting the ball mill speed (70-80r / min), time (16-20 hours), air cooling interval (0.4-0.6 hours) and ceramic ball diameter ratio (the mass ratio of 6mm and 3mm is 1:2) according to the preset program; Vacuum sealing system: ensures a sealed environment during powder mixing to avoid oxidation and contamination.
9. The system for preparing 3D printed in-situ cluster-reinforced aluminum alloy according to claim 7, characterized in that: The 3D printing module includes: Laser control system: used to adjust the laser spot size to 90-110μm and the laser scanning rate to 250-350mm / s; Printing equipment: Use heating printing equipment with a temperature range of 180-220°C to reduce the residual stress of the printing layer; Gas control system: can introduce high-purity nitrogen into the printing equipment to control the oxygen content in the equipment to be less than 100ppm; Positioning and strategy control module: supports automatic generation of printing paths, and selects checkerboard or strip printing strategies according to different models to achieve multi-directional distribution optimization of reinforced fibers.
10. The system for preparing 3D printed in-situ cluster-reinforced aluminum alloy according to claim 7, characterized in that: The heat treatment module comprises: Solution treatment unit: used for solution treatment of printed products at 325-375℃, with a treatment time of 2-3 hours; Rapid quenching unit: used for rapid quenching in water, with a transfer time of less than 10 seconds; Room temperature static unit: static for 11-13 days at room temperature of 15-35℃ for natural aging and microstructure optimization; Microscopic inspection module: integrated scanning electron microscope (SEM) and metallographic microscope (OM) to detect whether there are cracks inside the aluminum alloy, and use a mechanical testing machine to verify the tensile strength (530-545MPa) and elongation after fracture (≥7%).
Citation Information
Patent Citations
A method for 3D printing 7xxx aluminum alloy and its preparation
CN108330344B
Composite powder capable of achieving 7075 aluminum alloy crack-free SLM forming and preparation method and application thereof
CN110508805A
Special high strength 7-series aluminum-based composite material for 3D printing and preparation method thereof
CN111842890A
Cited By
Fusion manufacturing process for spaceflight aluminum alloy component
CN121156688A
Aerospace aluminum alloy component fusion manufacturing process
CN121156688B